Phase‐Field Modeling of Electromechanical Breakdown in Multilayer Ceramic Capacitors. Issue 4 (20th December 2018) - Cai, Ziming; Wang, Xiaohui; Li, Longtu
Abstract: Multilayer ceramic capacitors (MLCCs) are drawing increasing attention in the application of energy storage devices due to their high volumetric capacitance and improved energy density. However, electromechanical breakdown always occurs, especially under high operation voltage, which limits their application in high‐voltage circuit. In this work, a phase‐field electromechanical breakdown model is developed to give a fundamental understanding on the coupled electromechanical effect on the dielectric breakdown of MLCCs. The thickness‐dependent dielectric breakdown strength is well simulated through this phase‐field model. It is found that the dielectric breakdown strength and the patterns of final breakdown path is significantly influenced by the defect concentration and applied stress. An enhanced breakdown strength of MLCC is proved under either compressive or shear stress state. The model not only provides a mechanistic understanding toward the electromechanical breakdown in MLCCs, but also applies to all kinds of dielectrics and serves as guidance toward the design of high‐voltage dielectrics. Abstract : In this work, a phase‐field model is developed to give a fundamental understanding on the coupled electromechanical effect on the dielectric breakdown of Multilayer ceramic capacitors (MLCCs). The breakdown paths simulated agree well with the experimental observation. The findings that the effect of thickness, stress and defects on breakdown behavior can give a theoretical guidance when designing MLCCs.